A facile in situ approach to ion gel based polymer electrolytes for flexible lithium batteries. Issue 86 (28th November 2017) - Huang, Bingyu; Zhang, Youdi; Que, Mingming; Xiao, Yingbo; Jiang, Yaoquan; Yuan, Kai; Chen, Yiwang
Abstract : A simple, effective and low-cost in situ synthesis strategy was developed to produce cross-linked ion gel based polymer electrolyte for flexible lithium-based batteries with highly improved electrochemical performance and safety. Abstract : Inherent safety and stability issues arising from the use of traditional organic liquid electrolytes in lithium-based batteries are currently limiting their application to flexible electronics and large-scale energy storage from renewable sources. Gel polymer electrolytes (GPE) with chemical cross-linked structures and green ionic liquids as plasticizers represent a solution to this problem. In this study, a novel type of GPE with an interpenetrating polymer network (IPN-GPE) is prepared by a simple in situ thermally induced free radical polymerization. The as-prepared IPN-GPE with cross-linked structure displays a combination of high flexibility and deformability as well as thermal stability (over 310 °C). Moreover, IPN-GPE possesses a superior electrochemical stability window (5 V vs. Li + /Li) as well as a considerable ionic conductivity of 1.3 × 10 −3 S cm −1 at 30 °C. Therefore, with such an IPN-GPE gel electrolyte membrane, Li/IPN-GPE/LiFePO4 devices deliver superior stable charge/discharge profiles and remarkable cycling performance and rate capability. This simple, effective and low-cost in situ synthesis strategy makes IPN-GPE one of the most promising polymer electrolyte candidates for next generation rechargeable lithium-based batteries with highly elevated electrochemical performance and safety.